The teaching of literature in promoting students' critical thinking skills / Yusnita Md Yunus - Md Yunus, Yusnita (2008)
Promoting critical thinking skill through the teaching of literature is to improve the thinking skills of the students in which the students learn what to think and how to think through the subject (Norman, 1990; Clement & Lochhead, 1989 cited in Schafersman, 1991). This study aims the existing scenarios in today's classroom pertaining to the teaching of literature. Literature subject is seen as a difficult subject; therefore, the students are spoonfed. The focus of the study was to investigate whether the teaching of literature promotes critical thinking of the students. Thus the study determined the teachers' feedback on the subject, methodologies, literary texts and critical thinking skill. The benefits of the teaching of literature can be in the three forms; personal and emotional gains, learning gains and language gains. Apart from reading for enjoyment, literature promotes critical thinking skills when involves exploration of the texts. 36 teachers of six selected schools were the sample of this study. They were given a set of questionnaire to give their feedback. Three classes involved in the observation and six teachers were interviewed. Based on the findings, it was found out teachers are the best agents in teaching the subject as well as promoting critical thinking skill through the subject to the students. It was also found out that most of the teachers agreed that the teaching of literature is important and that the components contribute to the holistic development of the students. However the success of the implementation depended on the students' abilities. The study also determined that methodologies such as questioning, discussion and brainstorming techniques played important roles in ensuring the success of the subject in promoting critical thinking skills. The study demonstrated that the literature subject using the methods and techniques were capable in widening knowledge and broadening viewpoint of the students. It was also determined that the literary texts selected were relevant. It was also found that by using the literary texts selected and applying the best methods and techniques, critical thinking skills can be promoted in the teaching of literature.